Predicting Binding Free Energies for DPS Protein-DNA Complexes and Crystals Using Molecular Dynamics - Tereshkin, Eduard V.; Tereshkina, Ksenia B.; Krupyanskii, Yurii F. (Supercomputing Frontiers and Innovations, 2022)
The interaction between deoxyribonucleic acid (DNA) and deoxyribonucleic acid-binding protein from starved cells (DPS) in bacterial cells leads to intracellular crystallization of the genetic material of bacteria, which contributes to the survival of bacteria under stress factors, including antibacterial agents. Molecular modeling can help explain the molecular mechanisms of DNA binding to this protein. In this paper, we report a supercomputer simulation of the molecular dynamics of several types DNA-DPS complexes and crystals ranging from DPS+DNA dimer to DNA in periodic crystal channels of Escherichia coli DPS protein using a coarse-grained Martini force field. By modeling DNA of 24 base pairs, comparable in size to the diameter of the DPS protein, we use the slow-growth thermodynamic integration method to find binding protein-DNA free energy and discuss the contribution of ions and the length of trajectories sufficient for this type of simulations. The results obtained are important for further research in the field of simulation of biological DNA-protein crystals and the study of the molecular mechanisms of DNA interaction with the DPS protein.